Stalno strokovno izpopolnjevanje učiteljev razrednega pouka - Ivajnšič, Anja; Ivanuš Grmek, Milena (Revija za elementarno izobraževanje, 2009)
Improving professional qualifications for elementary school teachers. The article defines the roll of improving one's professional education as it applies to a teacher's professional growth. The first part of the article describes the external factors of a teacher's professional growth, with emphasis on improving their professional qualifications as a form of lifelong education for teachers. In the second part we show the results of our research that dealt with improving professional qualifications. This included different forms of improving one's professional qualifications, the frequency of participation at improvement programs, the type of improvement programs that teachers last participated in and the reasons for the low levels of attendance at programs for improving professional qualifications. We were interested in the differences between the teachers based on the amount of work experience they have (0 - 10 years, 11 - 20 years and more than 20 years of teaching experience). We determined that teachers with more than 20 years of teaching experience more frequently attend programs that improve professional qualifications.